2021
DOI: 10.3390/plants10040695
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Profiling of Flavonoid Abundance in Agave lechuguilla Residue-Valorizing under Explored Mexican Plant

Abstract: Agave lechuguilla waste biomass (guishe) is an undervalued abundant plant material with natural active compounds such as flavonoids. Hence, the search and conservation of flavonoids through the different productive areas have to be studied to promote the use of this agro-residue for industrial purposes. In this work, we compared the proportion of total flavonoid content (TFC) among the total polyphenolics (TPC) and described the variation of specific flavonoid profiles (HPLC-UV-MS/MS) of guishe from three loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 59 publications
2
14
0
1
Order By: Relevance
“…Flavonoids present a great diversity of biological activities, such as antioxidant effects or modulation of enzymatic activity among others [28]. Among the flavonoids previously identified in guishe crude extracts, Morreeuw et al, 2021 [13,14,29], reported the aglycon flavonols (quercetin, kaempferol, and myricetin), flavanone (hesperitin and naringenin), flavanols (catechin and epicatechin), anthocyanidins (cyanidin and delphinidin), and flavones (apigenin), which are known for their antioxidant and cardioprotective benefits [30]. In addition, the presence of methylated, sulfated, gallated, and glycosylated flavonoids in guishe [13] and A. lechuguilla leaves [30] suggested high antioxidant and immunomodulatory effects of the extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids present a great diversity of biological activities, such as antioxidant effects or modulation of enzymatic activity among others [28]. Among the flavonoids previously identified in guishe crude extracts, Morreeuw et al, 2021 [13,14,29], reported the aglycon flavonols (quercetin, kaempferol, and myricetin), flavanone (hesperitin and naringenin), flavanols (catechin and epicatechin), anthocyanidins (cyanidin and delphinidin), and flavones (apigenin), which are known for their antioxidant and cardioprotective benefits [30]. In addition, the presence of methylated, sulfated, gallated, and glycosylated flavonoids in guishe [13] and A. lechuguilla leaves [30] suggested high antioxidant and immunomodulatory effects of the extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it was observed that the presence of more than one glycoside moiety was influenced by regional factors. Therefore, those extracts that belonged to drought regions accumulated -di or -tri glycosylated flavonoids; these compounds can provide better tolerance to drought stress [30]. Other studies on other Agave species demonstrated that drought stress induced an increase in these compounds and other secondary metabolites [31,32].…”
Section: Extraction Methods Used To Recover Polyphenolic Compounds From Agave Agro-wastementioning
confidence: 84%
“…Later, Morreeuw, Castillo-Quiroz, et al [30] confirmed with HPLC-MS/MS that the hydroalcoholic mixture 70:30 (v/v) of A. lechuguilla Torr. was plentiful in mono-, di-and triglycosylated derivatives of apigenin, isorhamnetin, quercetin, and anthocyanins.…”
Section: Extraction Methods Used To Recover Polyphenolic Compounds From Agave Agro-wastementioning
confidence: 88%
“…In this context, bioprospecting studies have already described the benefits of A. lechuguilla extracts as antioxidant [ 30 , 31 ], anticancer [ 32 ], feed additive [ 33 ], antiparasitic [ 34 , 35 ], antibacterial, and antifungal [ 31 , 36 , 37 ]. Among the active agents of A. lechuguilla waste biomass, phenolic compounds have been widely characterized [ 38 , 39 , 40 , 41 ]. The diversity of chemical structures of the flavonoids found in A. lechuguilla bagasse explain the wide range of exhibited bioactivities.…”
Section: Introductionmentioning
confidence: 99%
“…At lower concentrations, the aglycone flavonols and flavanols presented, respectively, 15.57 and 7.91 µg/g DW, and showed antioxidant, anti-inflammatory, and anti-cancer effects [ 45 ]. The stated concentrations [ 40 , 41 ] and potential therapeutic effects suggest the downstream uses of the A. lechuguilla derivative products in cosmetic, nutraceutical, and pharmaceutical industries. In addition, the conservation of the flavonoid profiles through the productive areas confirmed the potential of this abundant plant material for the procurement of natural bioactive ingredients for commercial applications [ 41 ].…”
Section: Introductionmentioning
confidence: 99%